Crystal controlled CMOS oscillator for 13.56 MHz RFID reader - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (MIDEM, 2013)
A design procedure of CMOS integrated crystal oscillator for 13.56 MHz RFID is described in detail by using mathematical and Mentor Graphics VLSI design tools ADK-3. The system is designed by using CMOS 0.18 µm foundry rules and Level-3 transistor model. The frequency stability of the oscillator is created by using piezoelectric crystal. The designed CMOS crystal oscillator can be integrated with the other parts of the RFID reader systems during VLSI design. The computer-generated phase noise is showed -139.5 dBc/Hz at offset of 10 kHz and the power dissipation is 1.25 mW at power supply 2.2V.